Effect of Strategic Value Chain Positioning on Firm’s Performance: A Case of Pharmaceutical Supply Chain Firms in Kenya - Munyi, George Muriithi; Deya, Dr. Jared (European Journal of Business and Strategic Management, 2019)
Purpose: The purpose of the study was to assess effect of strategic value chain positioning on performance of Kenya's pharmaceutical firms. Methodology: Descriptive research design was used in this study. The target population for this study was members of staff drawn from the 152 pharmaceutical distributors in Nairobi. A critical sample of 10 firms was considered. Purposive sampling was used to arrive at an adequate sample size. The sample size was 40 people focusing on four officers per firm that is procurement, warehouse and logistics, marketing or customer service and finance managers. The data was collected using a self-administered questionnaire. Data analysis was done through descriptive and inferential statistics using SPSS with the main analysis tools being frequencies, means, standard deviation, and regression analysis. The results were then presented, discussed and interpreted. Finally, a summary, conclusions and recommendations were presented. The significance level was set at 0.05 and the confidence interval at 95%. Results: The findings of the study indicated that logistics management, operational practices, customer engagement and strategic procurement have a positive relationship with performance of pharmaceutical firms. Unique contribution to theory, practice and policy: It would be constructive for pharmaceutical firms to invest more in reducing operational costs to reduce the cost of operations through unnecessary reworks and ensure accuracy in operations through get it right the first time approach. They should form strategic alliances with their vendors so as to have a more improved working relationship characterized by electronic data interchange which ensure customers get what they want as when they need it this can be actualized through e-commerce. There is need for pharmaceutical firms to always set aside a substantial part of their resources for activities that spend a huge amount of total resources, and this entails the strategic procurement management. Procurement staff in the pharmaceutical firms should ensure that they strictly follow strategic value chain positioning procedures to ensure that goods supplied are of the right quality, in the right quantity, at the right time, to the right place from the right source at the most competitive price.